Is there a right place? The effect of within-leaf clutch location on offspring survival in a glassfrog - Francesca N. Angiolani-Larrea; Anyelet Valencia-Aguilar; Marina Garrido-Priego; Mélissa Peignier; Jaime Culebras; Lelis Jindiachi; José G. Tinajero-Romero; Juan M. Guayasamin; Eva Ringler (PLoS ONE, 2025)
The choice of where to breed can have fundamental consequences for offspring development and survival. Among amphibians, desiccation is one of the biggest threats to offspring survival, especially in species that deposit their clutches in terrestrial habitats. In several species, hydration of the clutch is ensured by a caregiving parent, but in species without prolonged care, site selection becomes critically important for securing constant external sources of hydration. We used the Spiny Cochran frog (Teratohyla spinosa), a Neotropical glassfrog in which females perform only short-term brooding to clutches, but then both parents leave the offspring, to test the effect of oviposition site selection within leaves on offspring development and survival. Previous observations have revealed that this species preferentially deposits eggs on the underside of leaves close to their margins. We hypothesized that T. spinosa strategically chooses this position to ensure clutch hydration during embryonic development, as water drops will slide from the edges to the tip of the leaves before dripping. To this end, we performed a clutch translocation experiment where we manipulated the location of clutches by placing them away from the leaf margin and compared their level of hydration, hatching time, and mortality rate to clutches that were kept on the leaf margins. Contrary to our expectations, we found that clutch hydration and mortality were not affected by the location on the leaf. These findings suggest that the observed clutch deposition on the edges of leaves in this species is not enhancing hydration conditions – at least under high humidity conditions.